Pulmonary infection by Mycobacterium riyadhense: first case report in United Arab Emirates - Sawan, Batool A.; Saleh, Leen O.; Al Shaltouni, Dina Z.; Sawan, Mohammad A.; Gawish, Shefa; Ahmed, Samar; Gomez-Seco, Julio; Otim, Michael E. (Frontiers in Medicine, 2024)
Mycobacterium riyadhense is an emerging slowly growing species that belongs to the group of nontuberculous mycobacteria (NTM) with approximately 20 cases reported worldwide. We highlight the first case of pulmonary infection by Mycobacterium riyadhense in United Arab Emirates (UAE). A 44-year-old female presented with chronic productive cough; a bronchial breathing pattern was appreciated on auscultation of her right upper lung. She was treated multiple times with allergic medications and antibiotics. Thorough investigations revealed Mycobacterium riyadhense and antitubercular drugs were started, eventually she was cured, however she had multiple relapses later. This case report holds a significant potential to make considerable contribution to the diagnosis of NTM, primarily because it presents the first documented case in UAE, as well as insights on how to address possible similar cases in the future.Mycobacterium riyadhense (M. riyadhense), is a newly recognized slow-growing, nonphotochromogenic NTM. M. riyadhense was first isolated from a patient in Riyadh, Kingdom of Saudi Arabia (KSA) who presented with maxillary sinus infection in 2009 (1). To-date, about 20 cases have been reported in the literature.Mycobacterium riyadhense seems to be capable of causing a spectrum of clinical presentations that are clinically indistinguishable from Tuberculosis (TB) (2). Despite pulmonary involvement being the most common form of non-tuberculous mycobacterial infections, a range of extrapulmonary presentations have been reported. The clinical and radiologic findings of pulmonary infection caused by M. riyadhense are indifferent from those caused by M. tuberculosis which is the most important human pathogen of the Mycobacterium tuberculosis complex (MTBC) (3).